PELUANG DAN TANTANGAN SARJANA SYARIAH DALAM MENGGELUTI PROFESI ADVOKAT PASCA UNDANG-UNDANG NOMOR 18 TAHUN 2003: Studi Kasus di Banda Aceh dan Aceh Besar - Zainuddin, Muslim (State Islamic University (UIN) Ar-Raniry, 2016)
Before the establishment of Act Number 18 of 2003 on the Advocate, the graduates from faculty of Sharia were treated unequal in law profession instead of law faculty’s students. The establishment of Act Number 18 of 2003 on the Advocate give chances for sharia faculty’s graduate to professionally become advocate. However this chance has not significantly been used by sharia’s graduates. The figure showed in 2007 that only seven of sharia’s graduates became advocate. The hesitation of choosing advocate has been caused by unwilling to do a vows profession, and also unable to hear public censure. It is also caused by curriculum earned in sharia faculty has not been integrated with other legal professions. Financially, advocate incomes has no certainty in term of sustainability. In society perspective being a civil servant are more promising rather than an advocate. Thus the sharia advocate association (APSI) has significant role to promoting and motivating sharia’s graduate to become advocate.